Designing Sustainable Working Lives and Environments: Work, Health and Leadership in Theory and Practice - Kerstin Nilsson (CRC Press, 2024)
Work is central to people's lives and the course of their life. The opportunities and chances an individual can have in their life are significantly connected to work. Individuals' work is also crucial for organisations, companies and for the whole of society. There is a constant need to make changes and readjustments of working life since these can deeply affect the individual and their employability. To make working lives more healthy, sustainable and attractive, being aware of the measures and changes that can be achieved in practice is of crucial importance. This book bridges the gap between the theories and explanatory models offered in research and actual work environments and workplaces. This book constitutes a theoretical framework that visualises the complexity of working life and increases the knowledge and awareness of individuals, companies, organisations and society regarding different factors and patterns. It aims to support individual reflections and joint discussions into daily operations on the individual, organisational and societal level. This book contains practical tools to use in daily working life that analyse possible risks in the work environment when planning measures and actions for health promotion. These practical tools are derived from the four spheres for action and employability in the SwAge model. Developed by the author, the SwAge model (Sustainable Working Life for All Ages) is a theoretical, explanatory model that explains the complexity of creating a healthy and sustainable working life for all ages. By using the SwAge model as a comprehensible framework, the reader will be able to visualise the complexity of factors that affect and influence whether people are able to and want to participate in working life and in the work environment, thereby contributing to increased employability. Designing Sustainable Working Lives and Environments is an essential read for students, researchers, work environment engineers, ergonomics and human factor specialists, occupational health and safety practitioners, business managers, HR staff, leadership decision-makers and labour union professionals.
Keywords: 650; Employability; Occupational Health; Meaningful work; Happiness at work; Working life; Mental health at work